Analysis of Stiffness Modulus of Asphalt Concrete Mixture by Using Artificial Aggregates - Gusti Made Bagus Baskara; Ervina Ahyudanari; I Nyoman Arya Thanaya (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
The type of damage to the pavement layer is cracking and permanent deformation. The mechanism of cracking in the pavement layer occurs because of the tensile force at the bottom of the pavement layer due to the wheel load of the vehicle. One parameter of a mixture to achieve strength and durability as needed is the relationship of stress and strain which shows the stiffness of a mixture. Indirect Tensile Strength is a method used to show the stiffness of a mixture. As infrastructure development in Indonesia continues to increase, the availability of natural aggregate materials is decreasing. One of the uses of geopolymer can be used as artificial aggregates to replace the depleted natural aggregates. The purpose of this study was to review the stiffness modulus of concrete asphalt mixture with the use of artificial aggregates made from geopolymer by using open gradations of BBA (Beton Bitumineux pour chausees Aeronautques). From the test results using the Dynapave UTM30 tool at 20 °Celsius and 60 °Celsius, stiffness modulus values of the asphalt mixture are 3542 MPa and 147 MPa. The increase in temperature causes a decrease in the stiffness modulus value of 96%, so that the increase in temperature will be accompanied by a decrease in the stiffness modulus.